2018
DOI: 10.1136/bmjgast-2018-000223
|View full text |Cite
|
Sign up to set email alerts
|

A male Korean who was diagnosed with chronic enteropathy associated withSLCO2A1(CEAS): case report with literature review

Abstract: ObjectiveTo further disseminate the nomenclature of chronic enteropathy associated with SLCO2A1 (CEAS), especially for physicians in China and Korea where the genetic feature of SLCO2A1 gene mutations related hypertrophic osteoarthropathy and pachydermia had been extensively studied. SLCO2A1 gene mutations related hypertrophic osteoarthropathy and pachydermia had been extensively studied.DesignA case report with literature review of SLCO2A1 gene mutations-related disorders.ResultsA 38-year-old Korean presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In 2018, a male Korean diagnosed with CEAS was reported as the first non-Japanese patient with the disease. 13 CEAS has now been reported in Japan, Korea, and China. 14 In particular, Huang et al 15 identified four new SLCO2A1 variants.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, a male Korean diagnosed with CEAS was reported as the first non-Japanese patient with the disease. 13 CEAS has now been reported in Japan, Korea, and China. 14 In particular, Huang et al 15 identified four new SLCO2A1 variants.…”
Section: Introductionmentioning
confidence: 99%
“…We searched the keywords of “CEAS”, “nonspecific multiple ulcers” or “ SLCO2A1 and enteropathy” in the PUBMED and reviewed the literatures. So far as we know, all of the patients reported in the literatures diagnosed with CEAS were almost Japanese, except two patients recently reported by Korea [ 3 ] and Chinese [ 4 ]. Thus, we hypothesized that CEAS was underestimated or was not recognized in Chines patients.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between PHO and CEAS is very close, and some of their clinical symptoms overlap, and the relationship between the two is worth exploring. Sun et al [32] believed that CEAS and PHO may be different manifestations of the same pathological process, and they are two sides of a coin. These ndings indicate that the clinical characteristics of SLCO2A1-related diseases are in uenced by other factors.…”
Section: Diseases Associated With Slco2a1mentioning
confidence: 99%